The Moderating Role of Leadership Support in Transformational Relationships Digital and Organizational Innovation towards Sustainable Performance - Agus Nadhif Faishal; Moudy Rosabilla (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the influence of digital transformation and organizational innovation on sustainability performance, with leadership support and digital literacy as supporting variables and the role of moderating effects in strengthening the relationship between variables. The research method used a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS- SEM) analysis. Data were collected through a questionnaire measured using reflective indicators for each construct. The results of the measurement model test indicate that all indicators have outer loading values above 0.70, thus being valid in measuring the latent construct. Structurally, digital transformation has a positive effect on sustainability performance with a path coefficient of 0.124, while organizational innovation shows a relatively weak effect with a coefficient of 0.006. Leadership support and digital literacy have a fairly strong positive effect on sustainability performance with a coefficient value of 0.586. In addition, the first moderation effect provides a strengthening of the relationship to sustainability performance with a coefficient of 0.154, while the second moderation effect shows a very small effect with a value of 0.032. The R² value of 0.670 indicates that the model is able to explain 67% of the variation in sustainability performance, while the remainder is influenced by other factors outside the research model. These findings confirm that the success of organizational sustainability performance does not only depend on digital transformation and organizational innovation, but is also greatly influenced by leadership support, digital literacy, and moderating mechanisms that strengthen the implementation of digital strategies. This research is expected to provide theoretical and practical contributions to organizations in designing digital- based sustainability strategies.